Schottky barrier diodes based on room temperature fabricated amorphous zinc tin oxide thin films. Issue 10 (13th June 2017) - Schlupp, Peter; von Wenckstern, Holger; Grundmann, Marius
Abstract: We report on Schottky barrier diodes on the amorphous oxide semiconductor zinc tin oxide (ZTO). The ZTO thin films were grown by pulsed laser deposition at room temperature. Reactively sputtered gold, nickel, platinum, palladium, and silver layers were used to realize the Schottky contacts. To enhance rectification, a thin semi‐insulating zinc tin oxide layer was introduced at the metal–semiconductor interface. The forward current–voltage characteristics of the platinum Schottky barrier diodes were modeled using thermionic emission theory. From temperature dependent measurements, the mean barrier heights of the diodes were determined to be 0.8 and 1.3 eV for diodes without and with a semi‐insulating layer, respectively. Further, the Pt–ZTO diodes were investigated by capacitance–voltage measurements and thermal admittance spectroscopy (TAS). We found that the obtained net doping density agrees with the free electron density determined from Hall‐effect measurements. TAS revealed two defect levels: one deep defect with an activation energy of 220 meV and one shallow defect connected to the carrier freeze‐out. Assuming scattering at potential barriers within the conduction band minimum being the dominant scattering mechanism in multi‐cation semiconductors at freeze‐out temperature, an activation energy of about 15–27 meV was derived.